Assessment of Molecular Measures in Non-FXTAS Male Premutation Carriers - Al Olaby, Reem R.; Tang, Hiu-Tung; Durbin-Johnson, Blythe; Schneider, Andrea; Hessl, David; Rivera, Susan M.; Tassone, Flora (Frontiers in Genetics, 2018)
At the molecular level, premutation carriers have increased expression levels of the FMR1 and the antisense FMR1 (ASFMR1) mRNAs. Both genes undergo alternative splicing giving rise to a number of different transcripts. Alteration in the alternative splicing process might be associated with FXTAS. In this study, we have investigated the correlation between objective measures of movement (balance and tremor using the CATSYS battery) and the expression of both the FMR1 and the ASFMR1 genes. In addition, we investigated whether their expression level and that of the ASFMR1 131bp splice isoform could distinguish between premutation carriers with FXTAS and non-FXTAS premutation carriers. Confirming previous findings, the expression levels of transcripts at the FMR1 locus positively correlated with the CGG repeat number and significantly differentiated the premutation carriers from the control groups. Furthermore, through comparison with age and gender matched controls, premutation carriers with and without FXTAS, showed a significant difference in the expression level of the ASFMR1 131bp splice isoform. However, there was no significant difference in the ASFMR1 131bp splice isoform expression level when comparing non-FXTAS and FXTAS premutation carriers. Finally, our results indicate significant group differences in CATSYS dominant hand reaction time and postural sway with eyes closed in premutation carriers compared to controls. In addition, a significant association between the tremor intensity and the expression level of ASFMR1 131bp splice isoform in premutation carriers compared to controls, was observed, suggesting a potential role in the pathogenesis of FXTAS.